Management of burns. Issue 7 (July 2021) - Kelly, Donna; Johnson, Christopher
Abstract: Burns represent a huge global economic and social burden produced by the severity of the injuries and the highly resource intensive treatment and rehabilitation required. The World Health Organization is aiming to reduce this with a programme of education, burns prevention and first aid measures. Assessment of the size and depth of a burn is paramount to determine the treatment each burn will require but can be challenging even for experts. Many developed countries have set up regional networks to centralize burns services but in the event of a major incident involving significant burns it is likely that these services would be quickly overwhelmed and support from the national and international community would need to be sought, as it has been in the past.